Encore [compact disc] - Jackson, Wanda, 1937- (Big Machine, 2021)
Queen of Rockabilly, Wanda Jackson, releases her final album featuring duets with Joan Jett, Elle King, Pistol Annies' Angalenna Presley, and Candi Carpenter.